Trends in Training Modern Technicians - Семенець, В. В.; Сайківська, Л. Ф.; Свид, І. В.; Мальцев, О. С. (NURE, MC&FPGA, 2019)
The paper considered procedural aspects affecting the quality of modern technicians training as well as practical examples of the implementation of procedures that affect it.
Keywords: technical training; cooperation; employers; VHDL; FPGA; MATLAB